2021
DOI: 10.1002/jmv.27115
|View full text |Cite
|
Sign up to set email alerts
|

TLR3 polymorphisms are associated with the severity of hand, foot, and mouth disease caused by enterovirus A71 in a Chinese children population

Abstract: Hand, foot, and mouth disease (HFMD) caused by enterovirus A71 (EV-A71) is a contagious viral disease, and toll-like receptors (TLRs) play essential roles in resisting the pathogen. The aim of this study was to assess the potential relationship between several TLRs polymorphisms and the HFMD severity in a Chinese children population. A total of 328 Chinese children with HFMD were included in the present study. The polymorphisms of TLR3 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In total, 270 relevant studies were initially performed. After layer-by-layer screening, 8 studies [11,[20][21][22][23][24][25][26] were finally included, including 9 case-control studies with a total of 3009 cases and 2131 controls. Coincidentally, all the included studies were about EV71 HFMD in the Chinese Han population.…”
Section: Literature Search and Quality Evaluation Resultsmentioning
confidence: 99%
“…In total, 270 relevant studies were initially performed. After layer-by-layer screening, 8 studies [11,[20][21][22][23][24][25][26] were finally included, including 9 case-control studies with a total of 3009 cases and 2131 controls. Coincidentally, all the included studies were about EV71 HFMD in the Chinese Han population.…”
Section: Literature Search and Quality Evaluation Resultsmentioning
confidence: 99%
“…A defective or decreased TLR3 response can lead to a weakening of the immune response against HBV 22 . It is reported that a number of TLR3 polymorphisms including rs5743313 are associated with severity of some viral diseases, that is, enteroviruses, influenza viruses, and HBV by reducing the efficiency of the virus recognition mechanisms 23–25 . TLR3 ‐rs5743313 is an intronic polymorphism, but is located near exon 4 which encodes transmembrane signal induction region of the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…22 It is reported that a number of TLR3 polymorphisms including rs5743313 are associated with severity of some viral diseases, that is, enteroviruses, influenza viruses, and HBV by reducing the efficiency of the virus recognition mechanisms. [23][24][25] TLR3-rs5743313 is an intronic polymorphism, but is located near exon 4 which encodes transmembrane signal induction region of the receptor. It is thought to play an essential role in receptor function by reducing the efficiency of the virus recognition mechanisms.…”
Section: Introductionmentioning
confidence: 99%